Internal migration and sexual partnerships and practices: Findings from a South African Cohort - Nyanisa , Yandisa (University of the Witwatersrand, Johannesburg, 2024)
Introduction There are high levels of geographic movement of people within South Africa’s borders, especially from rural to urban areas of the country. Such movements have an impact on sexual partnerships and practices. The aim of this study is to determine the relationship between internal migration and sexual partnerships and practices in a cohort of migrants and residents of the Agincourt study site (non-migrants) in South Africa’s rural northeast over two survey waves from 2018 to 2019. Methods This study used data from the Migrant Health Follow-Up Study (MHFUS) which commenced in 2017. The MHFUS is a 5-year cohort study that is nested within the Agincourt Health and Demographic Surveillance System (HDSS) longitudinal research platform. The cohort is based on a simple random sample of 3800 Agincourt HDSS residents and migrants aged 18 – 40. The Agincourt HDSS is located in a 420 square kilometre area of the Bushbuckridge district, Mpumalanga Province. Descriptive statistics, logistic and ordinal regression models were used to describe the characteristics of migrants and non-migrants in the cohort as well as sociodemographic factors associated with the number of sexual partners reported by participants, their type of recent sexual partners (whether a partner was regular or casual) and their calculated risk score (based on condom use and HIV testing). Results Sexual partnerships and practices differed by migration status and gender. A larger proportion of migrants than non-migrants had more than one partner in the last 12 months in both study waves. Of those migrants who had sexual partners in the last 12 months (n=1265), 11.2% had partners in both their place of origin and their current place of residence (migrant destination) in Wave 1. Nine or more total sexual life partners were reported more frequently by migrants (16.8%) compared to non-migrants (8.9%) in Wave 1. More males (31.6%) than females (5.3%) had two or more partners in Wave 1 and there were more males (15.6%) who reported having partners in iii both the origin and current locations compared to females (4.9%). Not using a condom was more common among non-migrants than migrants in both waves, with females being less likely to have used a condom in their last sexual intercourse compared to males. Ordinal logistic regression analysis indicated that the number of sexual partners in the last 12 months was associated with migration status, age, gender and employment status in Wave 1, while in Wave 2 it was also associated with level of education. Most recent partner (whether a partner was regular or casual) was associated with gender, education and employment in Wave 1 while associated with age, gender and employment in Wave 2. Risk score was associated with age and education in Wave 1 while associated with migration status, age, gender and education in Wave 2. Conclusion The study showed that sexual partnerships and practices differed by migration status and gender with non-migrants and females reporting more risky sexual practices compared to migrants and males. Internal migration can introduce risky behaviors that are related to sexual partnerships and practices. The study shows that the effect of migration can vary widely depending on factors such as gender dynamics, employment and education. A study of the relationship between internal migration and sexual relationships sheds light on this population's possible susceptibility to HIV/STIs. The evidence in this study also adds to the knowledge base needed for guidance in areas of prevention of STI, while future South African research focused on sexual partnerships and practices should incorporate measures of migration. Understanding these factors is essential for researchers, policymakers and health organizations involved in managing and providing support to migrants.
A research report submitted in fulfillment of the requirements for the Master of Science in Field Epidemiology, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Internal miration; sexual partnerships; sexual practices; South Africa; SDG-3: Good health and well-being